Effect of age, sex, area and management practices on cattle mortality in Rajshahi division, Bangladesh - Islam, Md. Reazul; Sarder, Md. Jalal Uddin; Hossain, K. M. Mozaffor; Islam, Md. Hemayatul; Uddin, Jashim (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The aim of the present study was to evaluate the effect of age, sex, location and management on cattle mortality rate in Rajshahi division of Bangladesh. Materials and methods: The study was conducted in 8 districts of Rajshahi division during July 2011 to June 2012. A total of 17,982 cattle heads were investigated based on age, sex, area. Data were collected from the cattle owners using a closed structured questionnaire. Tentative cause of cattle mortality was identified based on clinical signs, laboratory tests, history, ante-mortem and postmortem reports. Management practices of the cattle were also investigated. Results: Out of 17,982 cattle heads, 549 were found to be dead by various diseases, and an average mortality rate was 3.05%. Age-wise mortality rate of cattle revealed that the maximum mortality rate was found in the age group of <2 years (3.90%) and minimum was found in age group 2 to <8 years (2.36%). Sexwise splitting data showed that the higher mortality rate was observed in the female (3.15%) than the male (2.90%). Area-wise cattle mortality rate revealed that Rajshahi (3.29%), Natore (2.84%), Chapai Noawabganj (3.77%), Naogaon (3.48%), Bogra (2.57%), Joypurhat (2.84%), Pabna (1.84%) and Sirajganj (3.06%). The significantly highest (P<0.05) cattle mortality rate was found in Chapai Noawabgonj district (3.77%) and lowest was in Pabna district (1.84%). There is no significant difference (P>0.05) between the cattle mortality rate in Natore district (2.84%) and Joypurhat districts (2.84%). Conclusion: The overall mortality rate of cattle in Rajshahi division was found comparatively low. This might be due to improved management practices, better veterinary services, and awareness among farmers. However, cattle mortality rate in the age group <2-year is alarming due to bad management practices and disease. http://dx.doi.org/10.5455/javar.2016.c125